Life Cycle Rituals among the Rana Tharus of Far Western Nepal - Bist, Pirt Bahadur; Bist, Sita (KMC Journal, 2022)
This article focuses on the life cycle rituals of the Rana Tharu community of Far Western Terai. The Rana Tharus are one of the significant ethnic groups mostly concentrated in Kailali and Kanchanpur district of Far West region of Nepal. The objective of this study was to explore the life cycle rituals of the Rana Tharus. For this purpose, the Rana Tharu community of Kalagaudhi and Kalwapur village in Shukalaphanta Municipality, Kanchanpur district was selected as a study area. The research tools of this phenomenological qualitative research design include semi-structured interview, focus group discussion, informal discussion, observation and oral histories in data collection. This study narrates the life cycle rituals performed by the Rana Tharus elucidating peculiar type of death ritual Ghada (Sharaddha) performed only by the Rana Tharus. This death ritual is organized only after the death of the family member. In this ritual, a dummy prepared for the deceased person and the relatives of the deceased mourns for the night assuming dummy as the corpse of deceased person. The various social-cultural institution, traditions and practices followed by the Rana Tharus have developed social solidarity and cooperation among the Rana Tharus and have functioned properly for the maintenance of the livelihood of the Rana Tharus. The performance of life cycle rituals among the Rana Tharus has become a structure and system among them and is becoming an instrument of identity construction.